THE CONCEPT OF MARTYRDOM IN THE VIEW OF JAMĀ’AH ISLĀMIYAH IN INDONESIA - Muzayyin, Muzayyin (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
Religious radicalization is an irrefutable fact emerging mainly in the last decade. Several mass and suicide bombings (the nightclub Paddy's Pub in Bali, JW Marriot Hotel in Jakarta, Resort Police Mosque in Cirebon, Australian Embassy in Jakarta and several Churches in Indonesia) show this most clearly. The latest bombing in a mass building in Surabaya even had a thorough family as its actors. They and actors of other attacks claim that the bombing is of ways to put the doctrine of jihÄd fÄ« sabÄ«lillah into real life. It is therefore, the research employs a qualitative approach which aims to describe the concept of martyrdom as called amaliyat istisyhÄdiyah upon the perspective of Imam Samudera as one of JamÄâ€™ah IslÄmiyyahâ€™s activist which is allegedly responsible for a number of terror attacks in South East Asia. In addition, this research conclude that Martyrdom has no relation to suicide. Its aims at establishing KalimÄtullah and Islam, originating from the purest intention. While suicide is a hopeless deed performed by a person who kills himself for his own selfish reasonÂ